Specific targeting of a plasmodesmal protein affecting cell-to-cell communication. - Carole L Thomas; Emmanuelle M Bayer; Christophe Ritzenthaler; Lourdes Fernandez-Calvino; Andrew J Maule (PLoS Biology, 2008)
Plasmodesmata provide the cytoplasmic conduits for cell-to-cell communication throughout plant tissues and participate in a diverse set of non-cell-autonomous functions. Despite their central role in growth and development and defence, resolving their modus operandi remains a major challenge in plant biology. Features of protein sequences and/or structure that determine protein targeting to plasmodesmata were previously unknown. We identify here a novel family of plasmodesmata-located proteins (called PDLP1) whose members have the features of type I membrane receptor-like proteins. We focus our studies on the first identified type member (namely At5g43980, or PDLP1a) and show that, following its altered expression, it is effective in modulating cell-to-cell trafficking. PDLP1a is targeted to plasmodesmata via the secretory pathway in a Brefeldin A-sensitive and COPII-dependent manner, and resides at plasmodesmata with its C-terminus in the cytoplasmic domain and its N-terminus in the apoplast. Using a deletion analysis, we show that the single transmembrane domain (TMD) of PDLP1a contains all the information necessary for intracellular targeting of this type I membrane protein to plasmodesmata, such that the TMD can be used to target heterologous proteins to this location. These studies identify a new family of plasmodesmal proteins that affect cell-to-cell communication. They exhibit a mode of intracellular trafficking and targeting novel for plant biology and provide technological opportunities for targeting different proteins to plasmodesmata to aid in plasmodesmal characterisation.